Is the Public Domain Just?: Biblical Stewardship and Legal Protection For Traditional Knowledge Assets - Okediji, Ruth L. (The Columbia Journal of Law & the Arts, 2022)
The present debate over the legal treatment of traditional knowledge (TK) and genetic resources tends to rationalize the precarious conditions in which Indigenous peoples and local communities live. The debate is organized around the question whether TK should be treated as part of the public domain or whether property rights should apply. Both sides presuppose either a robust utilitarianism or else a narrow conception of historical redress for past injustices. This Article argues that both property and the public domain depend on the disruption of places, people, and cultures that may stand in the way of the material conditions industrialized societies use as a proxy for human welfare. The TK debate tends to avoid fundamental moral and justice-related aspects of TK protection, including the centrality of TK to Indigenous peoples’ cultural identities and ways (and quality) of life, as well as their long-term socioeconomic development. The Article proposes a theological framework of “biblical stewardship” rooted in imago Dei—the foundational concept informing Jewish and Christian understandings of human nature and social interaction—to address the socio-moral dimensions that are constitutive of TK systems and the institutional context in which they unfold. The biblical stewardship framework focuses on the cooperative and kinship arrangements that enable and sustain productive capacity for TK. It centers the need for Indigenous peoples and local communities to be able to develop and protect their knowledge assets as a precondition for those communities’ thriving, both in the present and the future. Moreover, biblical stewardship supplies a basis for accountability by Indigenous peoples and local communities for how their TK is managed, shared, and utilized within a broader framework of progress and the public good—including obligations that foreclose access and benefit-sharing agreements that may undermine conditions for flourishing of plant, animal, or human life.